Effect of lateral positioning on gastroesophageal reflux (GER) and underlying mechanisms in GER disease (GERD) patients and healthy controls. Issue 3 (29th November 2012) - Loots, C.; Smits, M.; OMARI, T.; Bennink, R.; Benninga, M.; VAN WIJK, M.
Abstract Background Posture has been shown to influence the number of transient lower esophageal sphincter relaxation (TLESRs) and gastroesophageal reflux (GER), however, the physiology explaining the influence of right lateral position (RLP), and left lateral position (LLP) is not clear. The aim of this study was to determine the influence of RLP and LLP on TLESRs and GERD after a meal in GER disease (GERD) patients and healthy controls (HC) while monitoring gastric distension and emptying. Methods Ten GERD patients and 10 HC were studied for 90 min (30 min test meal infusion, 30 min postprandial in either RLP or LLP (randomly assigned) and 30 min in alternate position). The study was repeated on a separate day in reverse position order. TLESRs, GER, and gastric emptying rate were recorded using manometry, multichannel intraluminal impedance, and 13C‐octanoate breath tests. Gastric distension was visualized by five serial gastric volume scintigraphy scans during the first 30 min. Key Results Gastroesophageal reflux, (GER) disease patients had increased numbers of TLESRs in RLP compared to LLP in the first postprandial hour [5 (4–14) and 4.5 (2–6), respectively, P = 0.046] whereas the number of TLESRs was not different in RLP and LLP [4 (2–4) and 4 (3–6), respectively, P = 0.7] in HC. Numbers of GER increased similar to TLESRs in GERD patients. In GERD patients, gastric emptying reached peak 13CO2 excretion faster and proximal gastric distension was more pronounced. Conclusions & Inferences In GERD patients, TLESRs, GER, distension of proximal stomach, and gastric emptying are increased in RLP compared to LLP. This effect is not seen in HC.